Sporothrix brasiliensis Gp70 is a cell wall protein required for adhesion, proper interaction with innate immune cells, and virulence - Leonardo Padró-Villegas; Manuela Gómez-Gaviria; Iván Martínez-Duncker; Luz A. López-Ramírez; José A. Martínez-Álvarez; Gustavo A. Niño-Vega; Héctor M. Mora-Montes (The Cell Surface)
Sporothrix brasiliensis is one of the leading etiological agents of sporotrichosis, a cutaneous and subcutaneous mycosis worldwide distributed. This organism has been recently associated with epidemic outbreaks in Brazil. Despite the medical relevance of this species, little is known about its virulence factors, and most of the information on this subject is extrapolated from Sporothrix schenckii. Here, we generated S. brasiliensis mutants, where GP70 was silenced. In S. schenckii, this gene encodes a glycoprotein with adhesive properties required for virulence. The S. brasiliensis GP70 silencing led to an abnormal cellular phenotype, with smaller, round yeast-like cells that aggregate. Cell aggregation was disrupted with glucanase, suggesting this phenotype is linked to changes in the cell wall. The cell wall characterization confirmed changes in the structural polysaccharide β-1,3-glucan, which increased in quantity and exposure at the cell surface. This was accompanied by a reduction in protein content and N-linked glycans. Mutant strains with high GP70-silencing levels showed minimal levels of 3-carboxy-cis,cis-muconate cyclase activity, this glycoprotein's predicted enzyme function, and decreased ability to bind laminin and fibronectin. These phenotypical changes coincided with abnormal interaction with human peripheral blood mononuclear cells, where production of IL-1β, IL-17, and IL-22 was reduced and the strong dependence on cytokine stimulation via mannose receptor was lost. Phagocytosis by monocyte-derived macrophages was increased and virulence attenuated in a Galleria mellonella larvae. In conclusion, Gp70 is an abundant cell wall glycoprotein in S. brasiliensis that contributes to virulence and proper interaction with innate immnune cells.